Advocating Community Economic Resilience Framework in Kemadang Food Barn, Gunungkidul, Yogyakarta: Accentuating the Social Capital Perspective - Rossalina Christanti; Hardo Firmana Given Grace Manik; Catarina Aprilia Ariestanti (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2023)
Agriculture is claimed as Indonesia’s strategic pillar sector. The existence of a community-based enterprise with a traditional business model is often seen as a weakness, while social capital is a strength to thrive. However, a well-managed conventional business model can become one of the foundations of a sustainable livelihood. This community service program wass carried out with the Artha Mandiri Group, which is domiciled in Kemadang Village, Gunungkidul, Special Region of Yogyakarta. This program aimed to increase the economic resilience of group members by empowering and growing business capabilities with their social capital as their fundamental strength. The empowerment method used in this program was Participatory Action Learning and Action Research (PALAR), which is considered an effective tool for strategically transforming paradigms. This method focused on a balance between progressive, collaborative practice accompanied by an action research foundation. The 6-month program has resulted in collaborative business competency learning practice for group members, emphasizing different processing methods to produce business line diversification. This group made flour from land-owned rice paddy harvests with the same quality as commercially produced. This achievement can also have an impact on business cost efficiency.